Digital Device Use, Computer Vision Syndrome, and Sleep Quality among an African Undergraduate Population - Prince Kwaku Akowuah; Augustine N. Nti; Stephen Ankamah-Lomotey; Asafo Agyei Frimpong; Jeremiah Fummey; Prince Boadi; Kofi Osei-Poku; Joseph Adjei-Anang (Advances in Public Health)
Background. The purpose of the study was to determine the prevalence of computer vision syndrome (CVS) and poor sleep quality among university students and assess the relationship between digital device usage, CVS, and sleep quality. Methods. A cross-sectional study including undergraduate students was conducted in Ghana between January–March 2020. Information on digital device use and CVS symptoms was collected using a structured questionnaire. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Logistic regression was used to determine the relationship between CVS and digital device use behavior, and linear regression analysis was used to explore the association between sleep quality and digital device use behavior. Statistical significance was set at p < 0.05. Results. Mean (SD) age of participants was 20.95 (1.68) years and most (54.97%) of them were females. The prevalence of CVS was 64.36%. Factors associated with CVS included hours of digital device use per day (OR = 4.1, p < 0.001), years of digital device use (OR = 3.0, p < 0.001), adjustment of digital device screen contrast to the surrounding brightness (OR = 1.95, p = 0.014), and presence of glare (OR = 1.79, p = 0.048). Prevalence of poor sleep quality was 62.43%. There was a significant association between poor sleep quality and number of years participants had used a digital device (p = 0.015) and the number of hours they used a digital device per day (p = 0.005). Conclusion. There is a high prevalence of both CVS and poor sleep quality among undergraduate students in Ghana. This represents a significant public health issue that needs attention.